Pengaruh Kualitas Produk Dan Social Media Marketing Terhadap Kepuasan Pelanggan Melalui Brand Trust - Rifqi Rijaluddin Arrayyan; Rivera Pantro Sukma (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The present research investigates how Product Quality and Social Media Marketing affect Customer Satisfaction, placing particular emphasis on the mediating function of Brand Trust in this relationship. The research targets consumers of Richeese Factory, selected for its strong digital presence and popularity among younger audiences. To analyze the data, the study utilized a quantitative research design by applying Structural Equation Modeling (SEM) through the Partial Least Squares (PLS) technique, executed using the SmartPLS 3 software. The analysis shows that both Product Quality and Social Media Marketing positively influence Brand Trust, but fail to produce a straightforward impact on Customer Satisfaction outcomes. Instead, Brand Trust functions as a crucial intermediary, exerting a direct influence on satisfaction levels while bridging the relationship between the independent variables and the final results. These results highlight the strategic importance of Brand Trust in improving customer satisfaction, especially within the highly competitive fast-food sector.